Factors Affecting Purchase Intention of Green Products among Households in Sarawak - Jocelyn Goh Swee Kee, Goh; Nur Nadhira, Baharuddin; Rossazana Ab-Rahim, Ab-Rahim (HRMARS, 2021)
This study aims to investigate the factors affecting purchase intention of green products among households. Green products are segregated from normal products in the market, and it is interesting to know what the society really thinks of those products, and what affects their desire and intention to purchase the green products. This study provides a research on what green products are, how they help the environment, and what affects consumers’ in the intention of buying these products. In this study, there are 2 specific objectives, including to examine the relationship between demographic factors and green purchasing intention, and assess factors affecting green purchasing intention. The methodologies which are used in this study includes multiple regression analysis and Pearson correlation test. The results of this study which concluded that demography, perceived value of products, and green branding are significant in affecting the purchase intention of green products serves as a guide for green product manufacturers on what is important to consumers in choosing products to buy.